Uplatňování a podoby přímé finanční pomoci fyzickým osobám na úrovni obcí - Hejzlarová, Eva M. (Univerzita Pardubice, 2011)
The paper focuses on the direct financial aid for individuals on the municipal level. Based on original research, it concludes that 12,5 % municipalities implement the tool and identifies three major types of aid:1) natural catastrophes aid, 2) aid while bridging the gaps of the system of social help guaranteed by state and 3) aid to reduct the social impacts of deregulation of the lease.
Keywords: social policy; municipality; direct financial aid; interest-free loans; natural catastrophe; reduction of the social impacts of deregulation of the lease